The Application of Rasch in the Validation of Corporate Citizenship Scale - Pillai, Kamala; Rasiah, R.; Williams, G. (2015)
This paper articulates the application of Rasch measurement in corporate citizenship research. With burgeoning expectation for greater corporate responsibility, studies have found that many companies continue to resort to green washing tactics in order to cope with growing pressures. In the absence of systematic adoption, the concept of corporate citizenship may remain rhetoric. The study is aimed at determining the fundamental attributes that facilitate the internalisation of corporate citizenship within companies. The study had to address two main challenges: First, the small sample size expected as it was based on primary data collection explicitly seeking the views of managers practicing corporate citizenship and second, as the study applied a multidisciplinary approach, there was a lack of prior systematic research available. Rasch modelling was applied to establish a psychometrically sound scale for the purpose of this study. A pilot test was followed with a larger sample set, where a total of 634 companies listed on the Malaysian Exchange were surveyed through online survey, of which 100 companies responded. The instrument’s reliability and validity were conducted using Winsteps version 3.49. The results of Rasch modelling analysis indicated the items measured reliability (r = 0.93) and persons measured reliability (r = 0.97). In addition, both item separation (3.51) and person separation (5.27) were found to be statistically significant. Further, all items measured in the same direction (point-measure correlation > 0.30) and valid items showed good item fit and constructed a continuum of increasing intensity. This study’s significance stands on its contribution towards the application of Rasch by future researchers in diverse social science and industrial settings in developing and validating sound scales.